Evaluation of the relationship of the climbing level of sport climbers with selected anthropometric indicators and diet composition - Przeliorz-Pyszczek, A.; Golabek, K.; Regulska-Ilow, B. (Central European Journal of Sport Sciences and Medicine, 2019)
Climbing is becoming more and more popular. During 2020 Olympic Games this discipline will be competed for the first time. Individualized diet plays a significant role among representatives of all sport disciplines. The aim of this research was to evaluate the correlation between the level of advancement of sport climbers, selected anthropometric indicators and diet composition. The study involved 36 women and 65 men practicing sport climbing who completed the food record and the survey on the most difficult climbing routes completed. Anthropometric measurements were collected. In the group of men statistically significant, positive correlation between the climbing level and the diet content of fiber, vitamin E, potassium, iron, zinc, and copper, was observed. In the group of women, a statistically significant positive correlation between the climbing level and the participation of vitamin C, potassium, magnesium and copper in the diet was observed. There was a positive correlation of protein, vitamin B2, B6, B12, D, phosphorus, magnesium, iron and copper content, and negative correlation between SFA content per 1,000 kcal of the diet and the climbing level of study participants. No statistical correlation was found between anthropometric parameters and advancement level